Physical-Chemical Characterization of Fruit Harvested at Different Maturity Stages of Grafted Yellow Pitahaya (Selenicereus megalanthus Haw.) - Jessica Sanmiguel; Valdemar Andrade; Yadira Vargas-Tierras; Iván Samaniego; Fernando Paredes-Arcos; Wilson Vásquez-Castillo; William Viera-Arroyo (Plants)
The physicochemical properties of fruits at different maturity stages using grafting technology are of great importance since grafting can alter the nutritional and functional parameters of the fruit. In this study, grafted yellow pitahaya (Selenicereus megalanthus Haw.) fruit, grown on live tutors, was evaluated from stages 0 to 5. The following response variables were recorded: fruit weight, diameter, and length; pulp weight with seed and peel; color; firmness; total soluble solids content; titratable acidity; pH; total flavonoid content; total polyphenol content; and antioxidant activity determined using FRAP and ABTS. The results show that fruits harvested from grafted plants have better physical characteristics such as fruit weight, diameter, and length. However, the total soluble solids content and titratable acidity were similar in fruits from grafted and ungrafted plants. The highest content of total polyphenols, flavonoids, and antioxidant activity determined by ABTS and FRAP were found in fruits at maturity stage 0, and the content decreased as the fruits ripened. A positive correlation was found between the total polyphenol content, total flavonoid content, and antioxidant capacity with protein content. The S. megalanthus grafting technique is a promising technology for sustainable production because it reduces pesticide use by combatting soil pathogens and not modifying fruit quality.